Clinical Features and Mortality of Endogenous Panophthalmitis in China: A Six-Year Study. (17th February 2022) - Qi, Meng; He, Lei; Zheng, Pengfei; Shi, Xiangyu
ABSTRACT: Purpose: To report the clinical features, treatment strategy, and mortality of patients with endogenous panophthalmitis (EP). Methods: Fifteen patients (16 eyes) diagnosed with EP from December 2012 to December 2018 were investigated with a standard protocol at a tertiary medical center of the largest eye center in Northern China. Mortality was followed up. Results: All participants were Han Chinese. The mean age was 58.3, 62.5% were male, and 93.3% were unilaterally involved. The average number of predisposing factors was 3.0. The top two predisposing factors were diabetes mellitus (DM, 93.3%) and pyogenic liver abscess (PLA, 66.7%). All patients initially presented at an ophthalmic emergency due to severe ocular symptoms. All patients were co-managed by relevant specialists and were admitted to medical or surgical wards instead of the eye center unless the systemic condition was well controlled. Only four eyes were eligible for vitrectomy. The mean follow-up duration was 12.5 months. The mortality rate was 0%. The predominant causative organism was Klebsiella pneumoniae (80.0%), and there were no positive fungal cases. Conclusions: EP is a rare, life-threatening disease. DM and PLA could predispose its development. The predominant causative organism was Klebsiella pneumoniae . The interdisciplinary cooperation system of the management of EP may reduce the mortality rate. Abbreviations :EP: endogenous panophthalmitis; EE: endogenous endophthalmitis; DM: diabetes mellitus; PLA: pyogenic liver abscess; ACI: acute cerebral infarction; UTI: urinary tract infection; ICU: intensive care unit; VA: visual acuity; LP: light perception; HM: hand motion; NLP: no light perception; K. pneumoniae: Klebsiella pneumoniae ; CT: computed tomography; MRI: magnetic resonance imaging; CRP: C-reactive protein; PCT: procalcitonin; FBG: fasting blood glucose; WBC: white blood cell; NEUT: neutrophil proportion; BDG: 1, 3-β-D-glucan; GM: galactomannan; IVI: intravitreal injection; PPV: pars plana vitrectomy; ILAS: invasive liver abscess syndrome; cps: capsular polysaccharide; CSF: cerebrospinal fluid; SD: standard deviation